Design and Analysis of Long Cylindrical Workpiece Fixtures - Taufik, Haryoni; Siti Umi Hani, Mohamed; Sivarao, Subramonian; Tajul Ariffin, Abdullah (2010)
This paper presents the design and analysis of long cylindrical workpiece fixtures for conventional milling machine in manufacturing. The proposed fixtures were designed for clamping, holding, and supporting workpiece securely during the machining process. The specification of workpiec for these fixtures is 10-50 mm diameter and 120 mm long. The simulation and analysis of the fixtures are described for V-Block part. Simulation results have been done by using Nastran/Patran and ANSYS CFX 10 and showed the optimize value of von misses stress and the deformation for the cylindrical fixtures. Deformation at the part cylindrical fixtures have been determined the visual resultant when analysis was successful done with the value of the von misses stress acquired. The safety factor results showed critical parts for the fixtures and determined the safe area. As a result, the milling fixtures for long cylindrical workpiece have been developed and tested for validation purpose.